Pengaruh Brand Image dan Minat terhadap Keputusan Siswa Sekolah di SMP Negeri 2 Jawa Maraja Bah Jambi - Susy Alestriani Sibagariang; Arya Pradana Damanik; Lasma Siagian (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2022)
This study aims to determine whether there is a positive and significant influence between brand image on student decisions, to find out whether there is a positive and significant influence between interest on student decisions, whether there is a positive and significant influence between brand image and interest in decisions. This type of research uses descriptive quantitative research methods, where this method aims to describe research results and draw conclusions. The population in this study amounted to 223 students using random sampling technique and calculated using the Slovin formula, the sample obtained was 143 respondents. The data analysis technique was carried out in several stages, namely data reduction, data presentation, and drawing conclusions. The results showed that the brand image variable had a influence on student decisions. Where the t-count value of the brand image variable (X1) is 2.446 > t-table 1.977 with a significance value of 0.016 <0.05. So it can be concluded that Ha1 is accepted. While the interest variable does not have a influence on student decisions. Where the t-count value of the interest variable (X2) -1.765 < t-table 1.977 with a significant value of 0.080 <0.05. So it can be concluded that Ha2 is rejected. For the results of the simultaneous F test, the f-count value is 5.315 > f-table 3.06 with a significant value of 0.006 <0.05, it can be concluded simultaneously that the brand image variable and the interest variable have a effect on the decision variable. These results indicate that Ha3 is accepted.